Leadership styles and gender relationship among public higher institutions in Malaysia / Raslan Nordin and Hazira Mohd Nasir - Nordin, Raslan; Mohd Nasir, Hazira (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia, 2017)
This study examines gender-based differences in the leadership style of academic leaders in public higher institutions Malaysia. The purpose of this study is to determine if there is any significant difference between the leadership style of male and female academic leaders and to examine the leadership styles of male and female academics leaders in public higher institutions Malaysia. The scope of this study is academic leaders who hold positions as Dean, Deputy of Dean and Head of Program from selected faculties of public universities. The research incorporated the Leadership Practices Inventory (LPI-IC) survey self response instrument, as well as a descriptive question that will be distributed to selected academic leaders. Due to the fact that Malaysian literature on gender differences and leadership styles is not being enriched, there is an urge for a researcher to produce robust and rigorous research examining the relationship between gender and leadership style among academic leaders. Thus this research is of practical significance because the leadership style could bring positive or negative impact on the quality of administration at the university level.